Identifying the influence of institutional factors on the R&D activities of Chinese SMEs. Issue 1 (2nd January 2016) - Cai, Di; Shen, Hao; Liu, Bing
Abstract : It is now well accepted that R&D activities are becoming a key driver of organizational change and performance growth for small and medium enterprises (SMEs). However, not all SMEs are successful at engaging in R&D activities. It is worthwhile to identify the determinants of SMEs' R&D activities. Researchers have mainly focused on organizational strategies and market environment conditions as the antecedents and barriers of SMEs' R&D activities while ignoring the role of the institutional context in which SMEs operate. In transitional economies such as China, institutional factors are key and important determinants of a firm's strategic decisions. Therefore, drawing on the institution-based view, this paper attempts to identify the influences of institutional factors on SMEs' R&D activities. Using a unique 2005 World Bank survey data-set comprising Chinese SMEs from 120 cities, the empirical results show that government intervention has a negative effect and that financial market development and legal system quality have positive effects on SMEs' R&D activities. Based on these findings, we argue that policymakers in transitional economies such as China should create favorable institutional environments for SMEs to foster innovation.